Analisis Sistem Kearsipan Digital di Seksi Pelayanan Kantor Pelayanan Pajak Pratama Pulogadung - Ana Yuliyana; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (CiDEA Journal, 2023)
Abstract. In the rapidly evolving era of information technology, digital records management is crucial for enhancing the efficiency of tax service tasks. This study thoroughly analyzes the existing digital archive system, emphasizing key aspects such as creation, storage, access, and management of digital records. Results reveal the potential of the digital archive system in the Tax Service Office Pratama Jakarta Pulogadung to boost records management efficiency and streamline information access. However, identified barriers include a limited understanding of the technology's full benefits and challenges in adapting to changes in work culture and traditional data management processes. These findings underscore the need for efforts to increase awareness and understanding of the benefits of effective digital records management. Furthermore, strategic development, focusing on training, cultural change, and technology integration, is crucial for optimizing digital archive systems. This research enhances our comprehension of the digital archiving system's role in improving the performance and efficiency of the Service Section of the Tax Service Office Pratama Jakarta Pulogadung, offering insights for future improvements in tax-related tasks.